(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
The article analyzes extension practices developed at Feevale University that interconnect Fashion, Design, museums, and communities, highlighting the role of extension curricularization in academic education and social transformation. Drawing from three experiences — the Zuzu Angel exhibition at the National Footwear Museum, the project Re-imagining Is Possible?, and the Da Rua Para’Nóia project — the study discusses how university extension can serve as a structuring axis for critical and decolonial pedagogies, repositioning the museum as a pedagogical territory and the community as a co-author of knowledge. Grounded in Paulo Freire, Orlando Fals Borda, Enrique Dussel, and Arturo Escobar, the research conceives extension as a poetic and emancipatory practice that weaves together teaching, research, and social commitment.